Atividade laboral de cirurgiões-dentistas do sistema público e privado de saúde: audição e qualidade de vida - Rodrigues, Nathana da Graca Sartori (2016)
This research aims to evaluate auditory and extra-auditory aspects to elaborate a hearing delineation and the quality of life of dental surgeons working in both public and private health systems, describing and comparing the results obtained. The purpose of the first one was to elaborate the hearing delineation, while of the second one, to assess these professionals’ quality of life. This is a descriptive observational cross-sectional study using a quantitative method. The sample consisted of 42 dental surgeons who were invited by the researcher in their own workplaces, subdivided into two groups with 21 professionals each (GI – public system and GII – private system). The procedures conducted in the research were a clinicaloccupational anamnesis, the Visual Analogue Scale when highlighted symptoms of tinnitus and/or dizziness, the World Health Organization Questionnaire for Quality of Life, and hearing evaluation tests, including Visual Inspection of External Acoustic Meatus, Acoustic Immittance Measurements, Pure Tone Audiometry, High Frequency Audiometry and Otoacoustic Emissions. The results of this investigation indicated that dental surgeons in the public system had a higher rate of auditory alterations in all hearing tests compared to the professionals working in the private system. Dental surgeons in both groups have good quality of life and are satisfied with their health. However, the expressive presence of auditory and extra-auditory symptoms due to exposure to physical (noise) and chemical occupational risks, as well as pain/discomfort due to ergonomic conditions, reinforce the need to incorporate preventive measures in dental clinics by the implementation of public policies on health and education. The awareness of professionals about the occupational risks and use of the hearing protector are the main preventive actions that can avoid or minimize the effects of noise on the health and quality of life of these workers.